TANTANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI ERA DIGITALISASI - Uliah, Rifatul; Seftiani, Wita; Mardlaatillah, Aina; Kurniawan, Wahyu; Yusria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digitalization has brought significant changes to education, including Islamic Religious Education (PAI), which has long been characterized by normative and traditional approaches, thus requiring adaptation to remain relevant to the learning characteristics of the digital-era generation. This study aims to analyze the challenges faced by the PAI curriculum in the digital era, including curriculum transformation, teacher readiness and digital competence, access and infrastructure availability, and the integration of Islamic values with digital literacy. This research employs a qualitative method through library research by analyzing books, scholarly articles, and educational policy documents using content analysis techniques. The findings indicate that digitalization offers opportunities for more varied, interactive, and flexible PAI learning through online platforms, multimedia resources, and blended learning models. However, the use of technology remains limited due to low teacher digital competence, inadequate infrastructure, and insufficient digital literacy among students. Additionally, the PAI curriculum faces substantive challenges related to integrating Islamic values with critical thinking skills, media ethics, and digital literacy to prevent students from falling into religious misinformation or value degradation. Therefore, the transformation of the PAI curriculum must be carried out comprehensively by strengthening teachers’ digital competencies, providing adequate infrastructure, and reconstructing the curriculum to combine Islamic spiritual values with 21st-century digital skills, ensuring that PAI learning remains relevant, meaningful, and adaptive to technological advancements.